Post-pandemic pedagogy a paradigm shift - Valenzano, Joseph M., III, 1978- (Lexington Books, 2021)
"Post-Pandemic Pedagogy: A Paradigm Shift discusses how COVID-19 upended the college and university pedagogical paradigm. This collection looks at what we thought we knew about good teaching, how those notions changed during the pandemic, and speculates on where we will go from here in our classrooms and on our campuses"--